Prophetic figures in late Second Temple Jewish Palestine: the evidence from Josephus - Gray, Rebecca (Oxford University Press, 1993)
This work examines the evidence from Josephus of prophetic figures in Jewish Palestine in the late Second Temple period, approximately 150 BC to AD 70